2015
DOI: 10.1080/1745039x.2015.1100866
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding a fish oil-containing diet to young, lean, adult dogs: effects on lipid metabolites, postprandial glycaemia and body weight

Abstract: The aim of this study was to determine the effect of feeding a fish oil (FO)-containing diet on lipid and protein metabolism, postprandial glycaemia and body weight in young, lean, adult dogs. Eight female Beagles were randomly assigned to one of two isonitrogenous and isoenergetic diets, Control or FO, in a crossover design. At the beginning of the experiment and at 30 and 60 d, a baseline blood sample was collected and the dogs then were fed their daily ration. Nitrogen balance began at 07:00 h on day 63 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
2
0
0
Order By: Relevance
“…Similarly, the cholesterol concentrations were significantly higher in the dogs after receiving corn oil, but not fish oil, but at the end of the 16-week trial they remained within normal reference values. These are in tune with a recent study where fish oil supplementation increased plasma triglycerides and ghrelin but did not appear to affect protein metabolism or postprandial glycaemia in adult lean dogs, whereas an increase in cholesterol concentration could be seen in the control diet group [95]. …”
Section: Discussionsupporting
confidence: 88%
“…Similarly, the cholesterol concentrations were significantly higher in the dogs after receiving corn oil, but not fish oil, but at the end of the 16-week trial they remained within normal reference values. These are in tune with a recent study where fish oil supplementation increased plasma triglycerides and ghrelin but did not appear to affect protein metabolism or postprandial glycaemia in adult lean dogs, whereas an increase in cholesterol concentration could be seen in the control diet group [95]. …”
Section: Discussionsupporting
confidence: 88%
“…Insulin (INS) is the main hormone that reduces serum glucose contents mainly by increasing its uptake of glucose in peripheral tissues [ 53 ], while glucagon (GC) increases serum glucose concentrations by promoting the production of glucose by cells from various substrates [ 54 ]. This study showed that lower contents of GLU and GC were both found in the FO groups, which is similar with previous results in dog [ 55 ]. In general, FO is rich in omega-3 fatty acids, which enhance the sensitive function of ADPN and lower serum glucose content [ 56 ].…”
Section: Discussionsupporting
confidence: 92%